Analysis of the Implementation of Public-Private Partnership (PPP) for the Lhok Guci Project from the Perspective of Environmental Law and Spatial Planning - Kurdi Kurdi; Cut Zulfahnur Syafitri (Faculty of Law, Universitas Pekalongan, 2025)
Indonesia, as a developing country, continually strives to improve the quality of life and prosperity of its people by enhancing various aspects ranging from health to economics. However, these efforts are hindered by inadequate infrastructure, which is crucial for the smooth distribution and implementation of government plans, thus impacting the overall standard of living and prosperity. Infrastructure needs in Indonesia can be categorized into economic and social infrastructure. Social infrastructure pertains to facilities designed to meet basic human needs, such as education and healthcare services, while economic infrastructure facilitates economic activities within a region, including roads and ports. Financing these infrastructural developments is a challenge, often necessitating innovative approaches like the KPBU scheme, where public-private partnerships play a significant role. The KPBU scheme has been instrumental in Indonesia's infrastructure development, as seen in projects like the Lhok Guci Irrigation System in Aceh Barat, Aceh Province. However, challenges arise, particularly concerning land acquisition and environmental compliance. The KPBU's success depends on adhering to environmental, social, and governance (ESG) principles, ensuring energy efficiency, gender equality, human rights protection, and legal compliance. Analyzing the Lhok Guci project within the ESG framework reveals its alignment with environmental goals and legal regulations. While land acquisition remains an issue, planned actions ensure compliance and minimal legal repercussions. Effective implementation strategies, such as thorough planning, environmental assessments, and legal approvals, are essential for successful KPBU projects.In conclusion, the KPBU model, when executed with environmental and legal considerations, can be successful in Indonesia, as demonstrated by the Lhok Guci project. Adhering to ESG principles and legal frameworks ensures responsible infrastructure development and mitigates potential challenges.